Analysis and biological relevance of advanced glycation end-products of DNA in eukaryotic cells - Breyer, Viola; Frischmann, Matthias; Bidmon, Clemens; Schemm, Annelen; Schiebel, Katrin; Pischetsrieder, Monika (Febs Journal, 2008)
Advanced glycation end-products (AGEs) of DNA are formed spontaneously by the reaction of carbonyl compounds such as sugars, methylglyoxal or dihydroxyacetone in vitro and in vivo. Little is known, however, about the biological consequences of DNA AGEs. In this study, a method was developed to determine the parameters that promote DNA glycation in cultured cells. For this purpose, the formation rate of N2-carboxyethyl-2′- deoxyguanosine (CEdG), a major DNA AGE, was measured in cultured hepatic stellate cells by liquid chromatography (LC)-MS/MS. In resting cells, a 1.7-fold increase of CEdG formation rate was observed during 14 days of incubation. To obtain insights into the functional consequences of DNA glycation, CEdG was introduced into a luciferase reporter gene vector and transfected into human embryonic kidney (HEK 293 T) cells. Gene activity was determined by chemiluminescence of the luciferase. Thus, CEdG adducts led to a dose-dependent and highly significant decrease in protein activity, which is caused by loss of functionality of the luciferase in addition to reduced transcription of the gene. When the CEdG-modified vector was transformed into Escherichia coli, a loss of ampicillin resistance was observed in comparison to transformation with the unmodified plasmid. These results indicate that CEdG accumulates in the genomic DNA of resting cells, which could lead to diminished protein activity. © 2008 The Authors.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.analys
Keywords: Advanced glycation end-products; DNA; Eukaryotic cells; Maillard reaction; N

Technologies in the Whole-Genome Age: MALDI-TOF-Based Genotyping - Humeny, Andreas; Vogel, Nicolas; Schiebel, Katrin (Transfusion Medicine and Hemotherapy, 2009)
With the decipherment of the human genome, new questions have moved into the focus of today's research. One key aspect represents the discovery of DNA variations capable to influence gene transcription, RNA splicing, or regulating processes, and their link to pathology. Matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS) is a powerful tool for the qualitative investigation and relative quantification of variations like single nucleotide polymorphisms, DNA methylation, microsatellite instability, or loss of heterozygosity. After its introduction into proteomics, efforts were made to adopt this technique to DNA analysis. Initially intended for peptide/protein analysis, it held several difficulties for application to nucleic acids. Today, MALDI-TOF-MS has reached worldwide acceptance and application in nucleic acid research, with a wide spectrum of methods being available. One of the most versatile approaches relies on primer extension to genotype single alleles, microsatellite repeat lengths or the methylation status of a given cytosine. Optimized methods comprising intelligent primer design and proper nucleotide selection for primer extension enabled multiplexing of reactions, rendering the analysis more economic due to parallel genotyping of several alleles in a single experiment. Laboratories equipped with MALDI-TOF-MS possess a universal technical platform for the analysis of a large variety of different molecules.